FROM STREET SINGER TO POPULAR MUSLIM PREACHER FIGURES - Julia, Julia (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2023)
This article seeks to examine the representation of Chinese Indonesians in New Media after the demise of Suharto’s New Order regimes. It takes root in the recent phenomenon in Indonesia as the “reappearance” of Chinese faces in popular Indonesian media by discussing the celebrities or public figures, and ordinary ‘man-on-the street’ of Chinese Indonesians, who are catapulted in the mainstream mass media and portrayed in popular television formats in particular such as reality-shows, talk-shows, news and variety shows. Based on participatory observation and in-depth-interview to the producers of several popular TV shows casting Chinese figures, this article argues that the political changes from authoritarian Suharto’s regimes which marginalized Chinese ethnicity to democracy has re-identified the representation of Chineseness in public sphere which contributes to more reception of Chinese identity at large in the country. This representation intermingles to produce the debates on religiosity and nationalism.